Digitalisasi Usaha Mikro Kecil dan Menengah dalam Membangun Ketahanan Bisnis di Era New Normal - Artanto, Aphief Tri; Kusnarto; Haryono, Nanang; Sholihatin, Endang (Journal of Governance and Administrative Reform, 2022)
Abstract The research objectives are (a) Knowing the readiness of Micro, Small and Medium Enterprises (MSMEs) in digitalization to build business resilience in the new normal era; (b) Explaining digital business innovation for MSMEs in building business resilience in the new normal era. This research is basic research with the theme of digital marketing from MSMEs in building business resilience in the new normal era. The MSME business can absorb a large workforce which has implications for reducing unemployment and improving the economy so that it has an impact on reducing the poverty rate as the goal of the Sustainable Development Goals. Conclusion Readiness to digitize MSMEs to Build Business Resilience in the New Normal Era: MSMEs are not fully ready to immediately switch to digital. Smartphones or laptops connected to the internet are quite a lot owned by MSMEs in running a business, but not all of them use them to market their products digitally. MSME Innovations in Building Business Resilience in the New Normal Era include: Adapting to new ways of working, integrated digital and technology systems, resilient supply chains, building business relationships; improve service quality; study business technology; social media understanding; selling on marketplaces. Abstrak Tujuan penelitian adalah (a) Mengetahui kesiapan Usaha Mikro Kecil dan Menengah (UMKM) dalam digitalisasi untuk membangun ketahanan bisnis di era new normal; (b) Menjelaskan digital business innovation UMKM dalam membangun ketahanan bisnis di era new normal.Penelitian ini merupakan penelitian dasar dengan tema Digitalisasi pemasaran dari UMKM dalam Membangun Ketahanan Bisnis di Era New Normal. Bisnis UMKM dapat menyerap tenaga kerja yang besar implikasinya dapat menurunkan pengangguran dan peningkatan ekonomi sehingga berdampak pada penurunan angka kemiskinan sebagaimana tujuan Sustainable Development Goals. Kesimpulan Kesiapan digititalisasi UMKM Untuk Membangun Ketahanan Bisnis di Era New Normal: UMKM ini tidak sepenuhnya siap untuk serta merta beralih ke digital. Smartphone atau Laptop terkoneksi internet cukup banyak dimiliki pelaku UMKM dalam menjalankan usaha, namun tak semua menggunakannya untuk memasarkan produk secara digital. Innovation UMKM Dalam Membangun Ketahanan Bisnis di Era New Normal diantaranya adalah: Beradaptasi dengan cara kerja yang baru, sistem digital dan teknologi terintegrasi, rantai pasokan yang tangguh, bangun relasi bisnis; tingkatkan kualitas layanan; belajar teknologi bisnis; pemahaman media sosial; jualan di marketplace.